Evaluation of Potential Disease‐Mediated Drug–Drug Interaction in Patients With Moderate‐to‐Severe Atopic Dermatitis Receiving Dupilumab - Davis, John D. (Clin Pharmacol Ther, 2018)
This open‐label drug–drug interaction study assessed whether blockade by dupilumab of interleukin (IL)‐4 and IL‐13 signaling affects the pharmacokinetics of drugs metabolized by cytochrome P450 (CYP450) enzymes. The pharmacokinetics of five CYP450 substrates given orally (midazolam, omeprazole, S‐warfarin, caffeine, and metoprolol, metabolized by CYP3A, CYP2C19, CYP2C9, CYP1A2, and CYP2D6, respectively) were evaluated before and 28 days after initiation of dupilumab treatment (subcutaneous 300 mg weekly) in 14 patients with moderate‐to‐severe atopic dermatitis. Dupilumab had no clinically relevant effects on the pharmacokinetics of CYP450 substrates, provided substantial clinical benefit, and was generally well tolerated. Only one serious adverse event was reported, an episode of systemic inflammatory response syndrome that resolved after treatment was discontinued. In summary, blockade of IL‐4/IL‐13 signaling in patients with type 2 inflammation does not appear to significantly affect CYP450 enzyme activities; the use of dupilumab in atopic dermatitis patients is unlikely to influence the pharmacokinetics of CYP450 substrates.